Accounting as a system of information resources generating: task transformation - A.Yu. Shchirska (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article studies the works of scientists in the field of various types of accounting and accounting methodology. The tasks of accounting are grouped according to the areas of their manifestation, the historical stages of the development of society and economic systems, the spheres of social and economic development, the types of management system, the basic economic concept chosen for the development of a particular country. The basic task of accounting is defined, i.e. the formation of qualitative accounting information, which in future will allow satisfy stakeholders. The quality is established to be the basis for evaluating accounting information for the purpose of matching the properties that users demand. The essence of the concept of «quality of accounting information» is determined by the set of information parameters that most accurately reflect the properties of the object of management under certain conditions of the environment of the functioning of economic agents and meet the information requests of participants in social and economic relations.